Digital Transformation Based on Touching Heart, Teaching Mind, and Transforming Life at SD Katolik 15 St. Laurentius Manado - Lianly Rompis; Julie Rante; Kristian Dame; Evi Kasiahe (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
Education is essential for humans to develop into meaningful, educated individuals. Education in Indonesia should play the right role in improving human resources. The best approach is to introduce science and technology in early childhood because, at this age, children still need guidance to understand and process information through reading. SD Katolik 15 St. Laurentius in Manado is a school with a strategic location that serves around 90 elementary students. This school has good potential to develop human resources and the learning process, with an adequate number of students and teachers, a well-built facility, and a spacious yard. To promote proper education for elementary students at SD Katolik 15 St. Laurentius in Manado, a team—comprising lecturers from the Electrical Engineering Study Program, lecturers from the PGSD (Elementary School Education for Teachers) Study Program at De La Salle Catholic University Manado, electrical engineering alumni, and students—was committed to conducting community service. The community service aimed to apply digital transformation based on Touching Heart, Teaching Mind, and Transforming Life through teaching on series and parallel circuits, a workshop on using the Canva application to create teaching materials in PowerPoint, and information flyers.